Appropriate vitamin D loading regimen for patients with advanced lung cancer. Issue 1 (December 2015) - Hoffer, L.; Robitaille, Line; Swinton, Nelda; Agulnik, Jason; Cohen, Victor; Small, David; Pepe, Carmela; Eintracht, Shaun
Abstract Background Most patients attending cancer clinics have hypovitaminosis D. Correcting or preventing this abnormal condition could mitigate the emotional and physical complications of their disease, but clinical trials of vitamin D therapy in this setting are hindered by the unavailability of safe, effective and practical loading dose regimens. Methods In this single arm open-label pharmacokinetic trial, outpatients with advanced lung cancer consumed 20, 000 IU vitamin D daily with the largest meal of the day for 14 days followed by 10, 000 IU per day for a further 7 days. Plasma concentrations of 25-hydroxyvitamin D [25(OH)D], parathyroid hormone, calcium, vitamin C and C-reactive protein were measured on protocol days 0, 14 and 21, and serum vitamin D binding protein (VDBP) concentrations on days 0 and 21. As a secondary objective, preliminary information was obtained regarding clinical effects of rapid vitamin D loading on mood and symptoms by administering appropriate questionnaires two times at baseline and after 14 and 21 days of vitamin D therapy. Results Of the 91 patients enrolled in the study, 85 % had hypovitaminosis D and 41 % had hypovitaminosis C. Plasma VDBP concentrations were in the normal range. The vitamin D load increased the average plasma 25(OH)D concentration to 116 ± 34 nmol/L (mean ± SD); the median concentration was 122 nmol/L (interquartile range 103–134); VDBP concentrations did not change. Final plasma 25(OH)D concentrations were subnormal (<75 nmol/L) for 13 % of the patients and sub-target (<120 nmol/L) for 44 % of them. In most cases, subnormal and sub-target 25(OH)D concentrations were attributable to obesity and/or a low baseline 25(OH)D concentration. Mood and symptom scores did not change significantly throughout the 3-week protocol. Conclusion Hypovitaminosis D and C are very common in outpatients with advanced lung cancer. A vitamin D load of 20, 000 IU per day for 14 days failed to achieve the target concentration in 44 % of the participants in this trial. These results suggest that a loading dose of 30, 000 IU per day for 14 days would be safe and effective for patients who are obese or at risk of severe hypovitaminosis D. The preliminary nature of the study design, and the failure to achieve target 25(OH)D concentrations for a large proportion of the patients, do not allow any firm conclusion about the clinical effects of correcting hypovitaminosis D in this patient population. Nevertheless, no evidence was obtained that partial correction of hypovitaminosis D greatly improved mood, reduced distress or relieved cancer-related symptoms. This trial was registered at clinicaltrials.gov as NCT01631526.